Pengaruh Jenjang Pendidikan Pemilik Usaha, Skala Usaha, dan Umur Usaha terhadap Penyusunan Laporan Keuangan pada UMKM di Kecamatan Paal Merah Jambi - Baining, Mellya Embun; Afrilicia, Nanda (ARZUSIN, 2025)
This study is motivated by the low level of financial statement preparation among Micro, Small, and Medium Enterprises (UMKM), which is presumed to be influenced by business characteristics such as the owner’s educational background, business scale, and business age. The aim of this research is to determine the effect of these three variables on financial statement preparation among UMKM in Paal Merah District, Jambi. Using a quantitative approach with a descriptive design, primary data were collected through questionnaires distributed to 99 UMKM actors. Data analysis was conducted using multiple linear regression, classical assumption tests, t-tests, and F-tests. The analysis results show that the owner’s educational background has no significant effect on financial statement preparation. In contrast, both business scale and business age have significant effects, both partially and simultaneously, as indicated by the F-test results. The coefficient of determination reveals that the three independent variables explain only 13.5% of the variation in financial statement preparation, while the remaining 86.5% is influenced by other factors not examined in this study. These findings suggest that an increase in business scale and age is more likely to encourage UMKM actors to pay attention to financial reporting practices than formal educational background. The implication is that assistance and training programs for UMKM should focus on practical and contextual aspects tailored to business needs in order to enhance financial reporting compliance.